THE ROLE OF ISLAMIC FINANCIAL INSTITUTIONS IN SOCIAL INTERMEDIARY SERVICES : EVIDENCE IN METRO CITY - Fitri Kurniawati (The Postgraduate of Institut Agama Islam Negeri Metro Lampung, 2020)
Islamic financial institutions are expected to be able to implement their roles as financial intermediaries and social intermediaries. But what happened in the city of Metro, the dominance of the contract on the practice of Islamic financial institutions only felt the benefits for the upper middle class. Besides that, innovative products that have not been able to reach the majority of the community are not optimal yet, where in the aggregate most of them are Muslims. So that the presence of Islamic financial institutions is considered the same as conventional, because it has not been able to answer the fundamental problems of society. Due to the limitations of researchers, the Islamic financial institutions that will be examined in this study are some Baitul Maal Wat Tamwil in Metro City. This research was conducted to analyze the strategies, procedures and product development of Islamic financial institutions in their role of social intermediation. Research is a field research with a descriptive analytical approach. Data collected using interview and documentation methods. Primary data was obtained from Islamic financial institutions (BMT) as social intermediaries in the community, namely the management and members of BMT. Secondary data were obtained from journals, research reports, books and articles. The analysis technique begins with data collection and reduction, data presentation and conclusion drawing. The results of this study are the role of Islamic financial institutions in social intermediation, namely as an intermediary that connects the aghniya and dhu'afa. The implementation procedure does not directly get commercial financing, but educational services using the tabarru agreement 'with social funds. Product development strategy, namely: establishing a special division in Islamic financial institutions and collaborating with social institutions around.